Efficient solvent- and temperature-tuned access to aldoxime ethers and phenolic functions by Pd-catalyzed C–O cross-coupling of aldoximes with aryl bromides and bromo-chalcones. (6th January 2020) - Reeta; Rangarajan, T. M.; Kaushik, Kumar; Singh, Rishi Pal; Singh, Manjula; Singh, Raj Pal
Abstract : A single method with a functionality switching option, to access oxime ethers and phenols, was developed for the first time for the Pd-catalyzed C–O cross-coupling of aryl bromides and bromo-chalcones with aldoximes. Abstract : A single method with a functionality switching option was developed for the first time for the Pd-catalyzed C–O cross-coupling of aryl bromides and bromo-chalcones with aldoximes. The ligand t BuXPhos (L2 ) was found to be an effective supporting ligand for the Pd-catalyzed coupling of aldoximes with bromo coupling partners. The functionality switching from oxime ethers to a phenolic or hydroxy group was driven by solvent or temperature. This method offers the products in good to excellent yields in short reaction times.